Estudo molecular da resistência a bacteriófagos líticos em Salmonella enterica subsp. enterica serovar Enteritidis - Nogueira, Letícia Amaral [UNESP] (2015)
Salmonella Enteritidis is a pathogen that belongs to the Enterobacteriaceae family and is often related to infections transmitted by food in humans, especially in children, elderly and immunosuppressed patients. The importance of this microorganism is because it's significant prevalence with worldwide distribution in lots of poultry, leading to serious implications for public health and poultry industry. Effective control of salmonellosis is a challenging because involves a complex animal handling and treatment with antibiotics that do not guarantee the elimination of infection. The use of lytic bacteriophages against bacterial infections (phage therapy) meets a demand for alternatives to the conventional antimicrobial treatment. However, the literature has reported the emergence of bacterial resistance to some lytic bacteriophages, such as in Salmonella sp. There are several mechanisms of bacterial resistance to phages, such as prevention of adsorption, blocking the injection of phage DNA, restriction-modification, abortive infection and the CRISPR/Cas System acquired immunity. Thus, this research aims to study in a molecular level the bacterial resistance of lytic phages isolated from pathogenic strains of Salmonella enterica subsp. enterica serovar Enteritidis (SE). Two mechanisms have been chosen: the CRISPR/Cas system and blocking of phage adsorption via LPS. From 22 SE strains, a total of 72 CRISPRs was identified with 14 different repetitive domains (DR), presenting a total of 551 spacers' sequences and cas1, cas2 and cas3 CRISPR associated genes. Cas 9 and cas 10 genes weren't identified. It was observed that phage lytic resistant strains have a higher total number of spacers in the CRISPR locus in relation to sensitive strains, and this difference was statistically significant. Phylogenetic analysis of cas genes from CRISPR/Cas system, of rfaC, rfaH, cpsG, manB, manc, lpxA, lpxB and lpxC genes (related to LPS) and of...